2016
DOI: 10.1002/cncr.29863
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported outcomes, body composition, and nutrition status in patients with head and neck cancer: Results from an exploratory randomized controlled exercise trial

Abstract: BACKGROUND:Patients with head and neck cancer experience loss of weight and muscle mass, decreased functioning, malnutrition, depression, and declines in quality of life during and after treatment. The purpose of this exploratory randomized study was to determine the optimal timing for the initiation of a lifestyle and progressive resistance exercise training intervention (during or after radiation therapy), as determined by intervention adherence and by comparing between-group outcomes across 24 weeks. METHOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
163
4
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(178 citation statements)
references
References 47 publications
(84 reference statements)
2
163
4
4
Order By: Relevance
“…The recruitment rate of 82% in the current study is high compared with what to our knowledge are the few exercise trials among patients with HNC conducted during treatment. Two previous randomized trials that evaluated the feasibility and efficacy of resistance training during RT both reported a recruitment rate of 55% . The main reasons for declining participation in these 2 studies were “too time‐consuming” and “feeling overwhelmed or emotional distress.” Also in the current study, we noted that although many patients appeared to be overwhelmed by the medical situation at the point of study request, few declined to participate in the study.…”
Section: Discussionmentioning
confidence: 99%
“…The recruitment rate of 82% in the current study is high compared with what to our knowledge are the few exercise trials among patients with HNC conducted during treatment. Two previous randomized trials that evaluated the feasibility and efficacy of resistance training during RT both reported a recruitment rate of 55% . The main reasons for declining participation in these 2 studies were “too time‐consuming” and “feeling overwhelmed or emotional distress.” Also in the current study, we noted that although many patients appeared to be overwhelmed by the medical situation at the point of study request, few declined to participate in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has indicated that cancer and nutritional status are closely linked 23,24. However, the underlying reasons why preoperative malnutrition causes a poor outcome remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This trial involved twice weekly group circuit classes taught by a certified exercise physiologist in urban hospital and community cancer centres, and home-based programmes that participants were instructed to complete at least two additional times per week (Capozzi et al, 2012). This group was an ideal sample from which to examine the changes in exercise preferences and barriers among HNC survivors since across the intervention period, participants significantly increased their average recommended physical activity minutes from below to above recommended weekly recommended minutes (Capozzi et al, 2016). Given the weight loss associated with HNC and its treatments, aerobic activity was limited to a brief warm-up before each strength workout, although participants were encouraged to progressively increase this to meet exercise guidelines as their weight stabilised.…”
Section: Participantsmentioning
confidence: 99%
“…This three-item questionnaire is widely used and has been successfully employed in previous HNC literature (Capozzi et al, 2016). This three-item questionnaire is widely used and has been successfully employed in previous HNC literature (Capozzi et al, 2016).…”
Section: Exercise Levelsmentioning
confidence: 99%